Low-energy extracorporeal shockwave therapy (ESWT) improves metaphyseal fracture healing in an osteoporotic rat model - Mackert, Gina A.; Schulte, Matthias; Hirche, Christoph; Kotsougiani-Fischer, Dimitra; Vogelpohl, Julian; Kneser, Ulrich; Harhaus-Wähner, Leila (PLOS ONE, 2017)
Purpose As result of the current demographic changes, osteoporosis and osteoporotic fractures are becoming an increasing social and economic burden. In this experimental study, extracorporeal shock wave therapy (ESWT), was evaluated as a treatment option for the improvement of osteoporotic fracture healing. Methods A well-established fracture model in the metaphyseal tibia in the osteoporotic rat was used. 132 animals were divided into 11 groups, with 12 animals each, consisting of one sham-operated group and 10 ovariectomized (osteoporotic) groups, of which 9 received ESWT treatment. Different energy flux intensities (0.15 mJ/mm2, 0.35 mJ/mm2, or 0.55 mJ/mm2) as well as different numbers of ESWT applications (once, three times, or five times throughout the 35-day healing period) were applied to the osteoporotic fractures. Fracture healing was investigated quantitatively and qualitatively using micro-CT imaging, quantitative real-time polymerase chain reaction (qRT-PCR) analysis, histomorphometric analysis and biomechanical analysis. Results The results of this study show a qualitative and quantitative improvement in the osteoporotic fracture healing under low-energy (energy flux intensity: 0,15 mJ/mm2) ESWT and with fewer treatment applications per healing period. Conclusion In conclusion, low-energy ESWT seems to exhibit a beneficial effect on the healing of osteoporotic fractures, leading to improved biomechanical properties, enhanced callus-quantity and -quality, and an increase in the expression of bone specific transcription factors. The results suggest that low-energy ESWT, as main treatment or as adjunctive treatment in addition to a surgical intervention, may prove to be an effective, simple to use, and cost-efficient option for the qualitative and quantitative improvement of osteoporotic fracture healing.
Published: December 12, 2017
Gesehen am 30.07.2018